Neurological Biology and Its Relation to Education: Implications of Neuroscience For Learning Practice in the 21st Century - Dahlia Farina; Maltifal Maltifal; Agusrianto Agusrianto; Ahmad Lahmi; Julhadi Julhadi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study examines the relationship between neurobiology (neuroscience) and modern educational practices. Advances in neuroscience over the past two decades have opened new insights into how the human brain learns, stores memory, and processes information. This review aims to: (1) describe the neurobiological mechanisms underlying the learning process; (2) identify the implications of neuroscience findings on learning strategies; and (3) formulate evidence-based recommendations for educators. A systematic literature review of 45 articles published between 2010-2024 from Scopus, Web of Science, and Google Scholar databases was conducted. Results indicate that neuroplasticity, the role of emotions in memory consolidation, and sleep cycles have direct relevance to learning effectiveness. Neuroscience-based learning strategies such as spaced repetition, retrieval practice, and multimodal learning are proven to enhance long-term knowledge retention. These findings affirm the need to integrate neuroscience knowledge into teacher training curricula and instructional design.